Pengaruh Teknologi Informasi, Stres Kerja dan Kompensasi Finansial terhadap Kinerja Karyawan melalui Employee Engagement di Masa Pandemi Covid19 (Studi Kasus PT “X”) - Sulistyojati, Putrianti; Pracoyo, Antyo; Harun, Paulina; Rasyid, Soelaiman (STIE Indonesia Banking School, 2024)
The company's readiness to conduct business in the midst of a pandemic is a big challenge for all businessman in the world including Indonesia and especially in Jakarta as a business center in Indonesia. Not only must maintain business in times of pandemic, but also must struggle with new things related to technology such as providing internet networks for work-at-home facilities, procedures to coordinate using technology and others. This study aims to examine the effect of information technology, job stress and financial compensation on employee performance through employee engagement as an intervening variable. The sample in this study consisted of 109 respondents who were permanent employees of PT X. The method of analysis used was Structural Equation Modeling (SEM). The results of this study indicate the results of a positive influence between information technology and employee performance. Job stress has no positive and insignificant effect on employee performance. Financial compensation is proven to have no positive and insignificant effect on employee performance. Information technology is proven to have no positive and significant effect on employee engagement. Work stress was proven to have no positive and significant effect on employee engagement. Financial compensation has a positive but insignificant effect on employee engagement. Employee engagement has a positive and significant impact on employee performance. Information technology has no significant effect on employee performance through employee engagement. Job stress has no significant effect on employee performance through employee engagement. Financial compensation has a positive effect on employee performance through employee engagement.